2022
DOI: 10.3389/fphys.2022.844539
|View full text |Cite
|
Sign up to set email alerts
|

H2S Protects Against Immobilization-Induced Muscle Atrophy via Reducing Oxidative Stress and Inflammation

Abstract: Chronic inflammation and oxidative stress are major triggers of the imbalance between protein synthesis and degradation during the pathogenesis of immobilization-induced muscle atrophy. This study aimed to elucidate the effects of hydrogen sulfide (H2S), a gas transmitter with potent anti-inflammatory and antioxidant properties, on immobilization-induced muscle atrophy. Mice were allocated to control and immobilization (IM) groups, which were treated with slow (GYY4137) or rapid (NaHS) H2S releasing donors for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…H 2 S inhibits ROS-mediated CHOP apoptotic signaling in endoplasmic reticulum stress (Zhu et al, 2022). Administration of GYY4137 or NaHS improved overall antioxidant capacity and raised Nrf2 levels, which together dramatically reduced immobilization-induced oxidative stress (Xu et al, 2022). Additionally, the level of phosphorylated p47 phox was signi cantly reduced after NaHS infusion into RVLM, which would reduce the enzymatic activity of NADPH oxidase.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…H 2 S inhibits ROS-mediated CHOP apoptotic signaling in endoplasmic reticulum stress (Zhu et al, 2022). Administration of GYY4137 or NaHS improved overall antioxidant capacity and raised Nrf2 levels, which together dramatically reduced immobilization-induced oxidative stress (Xu et al, 2022). Additionally, the level of phosphorylated p47 phox was signi cantly reduced after NaHS infusion into RVLM, which would reduce the enzymatic activity of NADPH oxidase.…”
Section: Discussionmentioning
confidence: 99%
“…In an endotoxic shock model, H 2 S can block the release of TNF-α and IL-1β. Injections of NaHS or GYY4137, according to Xu et al, reduced the in ltration of CD45 + leukocytes brought on by immobilization while reducing the expression of proin ammatory biomarkers in skeletal muscle (Xu et al, 2022). Another study demonstrated that H 2 S inhibits the activation of the NLRP3 in ammasome, which slows the development of diabetesaccelerated atherosclerosis and protects endothelial cells (Zheng et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the mechanism to generate the heme ferryl compound II and a thiyl radical, HS • , is diferent from the model proposed by Nicholls [57], the calculated energetic data indeed supported their hypothesis of the reaction between hem-eFe(IV)=O and the HS • to produce sulfheme. Furthermore, contrary to the classical peroxidative reaction of heme proteins with H 2 O 2 [60,61],the absence of the heme Cpd-I radical [Fe(IV)=O +• ] in sulfheme formation through reaction (1a) [53,59] supports the antioxidant role of hydrogen sulfde [18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 90%
“…Reduced H 2 S levels are also related to Parkinson's, Alzheimer's, and atherosclerosis [14,15]. Furthermore, H 2 S has been correlated with chronic diseases [16,17], infammation [18,19], oxidative stress [20][21][22][23][24][25], oral diseases [26], glaucoma [27], subarachnoid hemorrhage [28], infertile men [29], arterial oxygen saturation [30], and skin diseases [31].…”
Section: Introductionmentioning
confidence: 99%